Examination of evaluative threat in worry: Insights from the Error-Related Negativity (ERN). (30th December 2018) - White, Evan J.; Grant, DeMond M.; Taylor, Danielle L.; Frosio, Kristen E.; Mills, Adam C.; Judah, Matt R.
Highlights: Uncertain evaluative threat distractors result in a reduced ERN amplitude. Worry was associated with higher ERN amplitude post manipulation. Negative evaluative threat distractors did not demonstrate a significant influence on ERN amplitude. Abstract: Recent research suggests atypical error-monitoring is important to understanding pathological anxiety. Because uncertainty is a transdiagnostic factor associated with anxiety and related disorders, recent research has begun to examine the influence of uncertainty in error-monitoring. Moreover, task irrelevant threat has been shown to influence cognitive performance in individuals with maladaptive anxiety. The current study aims to merge these literatures by examining the influence of task-irrelevant uncertain evaluative threat on error-monitoring using an event-related brain potential, the error-related negativity (ERN). Considering extensive literature indicating a relationship between worry and the ERN, worry was included as a continuous predictor in the analyses. Participants were randomly assigned to either a condition of negative or uncertain evaluative threat to determine their influence on error-monitoring in a Flankers task. Results for the ERN suggest that the ERN was significantly reduced only for the uncertain evaluative threat condition. The current study suggests that uncertain evaluative threat distractors result in a subsequent reduction in error-monitoring. This is consistent with literature suggesting that anxiety impairs inhibition of attentional processing of task irrelevant threatening information. This study adds to the burgeoning literature on the malleability of the ERN. Future research is needed to determine the mechanisms underlying this effect.